Permeability of blood-tear barrier to fluorescein and albumin after application of platelet-activating factor to the eye of the guinea pig - J. L. Van Delft; F. Meijer; J. A. Van Best; N. J. Van Haeringen (Hindawi Limited, 1997)
One of the inflammatory responses of the eye to local application of platelet-activating factor (PAF) is oedema of the conjunctiva, caused by extravasation of plasma. Aim of the study was to investigate if fluorescein would leak from the blood into the tears together with plasma protein after application of PAF to the eye. Fluorescein was given intraperitoneally 30 min prior to application of 25 μl of 0.1% solution of PAF. Thirty min after PAF the tear film was collected by washing the surface of the eye with 25 μl of phosphate buffered saline (PBS). Fluorescein in eye washings and in plasma was measured by fluorophotometry and albumin by immunodiffusion. Both fluorescein and albumin appeared in a related fashion in tears, being absent in washings of placebo-treated control eyes. Extravasation of fluorescein can be used as a measure for plasma leakage in the conjunctiva with the advantage over the Evans Blue method that the former is a non-invasive method.